Determination of total flavonoid content of extract and fractions of mangrove leaves (Avicennia marina) - Annas, Zulfiana Fitrianingrum; Muliasari, Handa; Deccati, Rizqa Fersiyana; Permatasari, Lina; Mukhlishah, Neneng Rachmalia Izzatul (Universitas Muhammadiyah Mataram, 2023)
Mangrove plants (Avicennia marina) come from the Avicenniaceae family. The leaves have antioxidant, antiviral and antibacterial activity caused by the content of secondary metabolites in mangrove leaves in the form of flavonoid compounds. Research on the total flavonoid content of 96% ethanol extract and the water, ethyl acetate, and n-hexane fractions of A. marina leaves has never been carried out. The aim of this study was to determine the total flavonoid content in extracts and fractions of A. marina mangrove leaves by UV-Vis spectrophotometry method. Extraction was carried out using 96% ethanol solvent by sonication method, then fractionation was carried out using the liquid-liquid fractionation method. The extracts and fractions obtained for their secondary metabolites were identified by test tube and thin layer chromatography and then the total flavonoid content was determined by the colorimetric method. Mangrove leaf extracts and fractions contain secondary metabolites of flavonoids, phenolics, saponins, steroids, triterpenoids, and alkaloids. The results of thin layer chromatography confirmed the results of the tube test that mangrove leaf extracts and fractions contained flavonoid compounds. Total flavonoid content in 96% ethanol extract, water fraction, ethyl acetate fraction, and n-hexane fraction of A. marina mangrove leaves were 19.37; 3.07; 11.30; and 56.62 mg quercetin equivalent/gram sample. In conclusion, the total flavonoid content of A. marina leaves was high, thus supporting its activity as an antioxidant.